2008
DOI: 10.1103/physrevb.77.235419
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of carbon peapods: Elliptical deformation of nanotubes and aggregation of encapsulatedC60

Abstract: The energetics of large diameter carbon nanotubes encapsulating C 60 molecules ͑peapods͒ have been studied by using the local density approximation in the density-functional theory ͑DFT͒. We find that the energy gain ascribed to the encapsulation of C 60 increases under the elliptical deformation of the nanotubes compared to that for the nanotubes with circular cross section. The energy cost of the deformation of nanotubes is found to be less than 10 meV per atom and is found to be the largest for the ͑20,20͒ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 40 publications
5
25
0
Order By: Relevance
“…We observed that at 700 °C and under 300 keV electrons, armchair edges are more stable than zigzag edges, in agreement with quantum mechanical calculations. 29 At room temperature and under 80 keV electrons, similarly to Girit et al, we also observed long zigzag edges. 5…”
supporting
confidence: 89%
“…We observed that at 700 °C and under 300 keV electrons, armchair edges are more stable than zigzag edges, in agreement with quantum mechanical calculations. 29 At room temperature and under 80 keV electrons, similarly to Girit et al, we also observed long zigzag edges. 5…”
supporting
confidence: 89%
“…In this regard, the huge number of theoretical works that recently appeared in the literature on GNRs [17][18][19][20][21][22][23][24][25][26][27] has almost exclusively focused on single-hydrogen saturation of the edge carbon atoms. This was mainly due to the surprising discovery of spin-polarized electronic states localized on the edges of zigzag GNRs 17,18 , possibly turning them into half-metals under high electric fields 19,20 , and spurring great interest in view of possi-ble applications in future spintronics.…”
Section: Introductionmentioning
confidence: 99%
“…We note that the relative stability of zigzag versus armchair edges in graphene has been theoretically debated [13][14][15][16] , with different conclusions reached in different calculations. Experimentally, both armchair and zigzag oriented edges (which may still have microscopic roughness) have been found in graphene prepared by different methods.…”
mentioning
confidence: 99%